2017
DOI: 10.3390/en10081129
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dynamic Melting Process in a Thermal Energy Storage Unit Using a Helical Coil Heat Exchanger

Abstract: Abstract:In this study, the dynamic melting process of the phase change material (PCM) in a vertical cylindrical tube-in-tank thermal energy storage (TES) unit was investigated through numerical simulations and experimental measurements. To ensure good heat exchange performance, a concentric helical coil was inserted into the TES unit to pipe the heat transfer fluid (HTF). A numerical model using the computational fluid dynamics (CFD) approach was developed based on the enthalpy-porosity method to simulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The experimental results showed that the heat transfer time was reduced by approximately half when changing the operating mode from case 8 (57 min) to case 5 (27 min). The results of the present work agreed with the results obtained by Le et al [15] and Yang et al [27]. In their papers, they reported that the charging time for the heat transfer fluid was also reduced by half when the inlet temperature of the heat transfer fluid increased from 55 C to 70 C, and the mass flow rate of the fluid remained constant.…”
Section: Temperature Fields Of Water In the Fish Tanksupporting
confidence: 92%
“…The experimental results showed that the heat transfer time was reduced by approximately half when changing the operating mode from case 8 (57 min) to case 5 (27 min). The results of the present work agreed with the results obtained by Le et al [15] and Yang et al [27]. In their papers, they reported that the charging time for the heat transfer fluid was also reduced by half when the inlet temperature of the heat transfer fluid increased from 55 C to 70 C, and the mass flow rate of the fluid remained constant.…”
Section: Temperature Fields Of Water In the Fish Tanksupporting
confidence: 92%
“…As already mentioned, the heat transfer rate between the HTF and PCM increased with an increasing temperature difference between them and with an increasing HTF flow rate. However, many scientists, for example Youssef et al [25], Yang et al [32], and Anish et al [33], concluded that changing the HTF inlet temperature impacts more the phase change time than changing the HTF flow rate. Furthermore, Khan and Khan [34], Wu and Fang [35], and Wu et al [36] found that the phase change time reduction gets smaller as the HTF flow rate increases.…”
Section: The Influence Of Htf Inlet Parametersmentioning
confidence: 99%
“…It has been extensively reported that nanofluids and working fluid mixed with nanoparticles possess superior thermal conductivity to that of pure fluid [5][6][7][8][9][10][11]. In particular, nanofluids have been applied in energy storage systems to enhance the thermal conductivity of the energy storage materials [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%